Augmented Reality Buku Cerita Anak Sebagai Media Mendongeng Pada Komunitas Bali Mendongeng Berbasis Android - I Made Adi Krisma Dinata; Harsemadi, I Gede (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
The culture of reading fairy tale books by parents and children is very difficult to find, so it becomes a important issue in the Bali Mendongeng Community to develop media to preserve the storytelling culture. This study aims to utilize technology as a solution to solve problems regarding books as a storytelling medium. One of technologies can be used to make books into fun storytelling media for children is Augmented Reality. Therefore, an Augmented Reality-based children's story book illustration was made to make storytelling more interesting. The research development method is the Multimedia Development Life Cycle. This research resulted a story book entitled